2017
DOI: 10.1590/1516-4446-2016-2058
|View full text |Cite
|
Sign up to set email alerts
|

Chronic dosing with mirtazapine does not produce sedation in rats

Abstract: Objective: Sedation/somnolence are major side effects of pharmacotherapies for depression, and negatively affect long-term treatment compliance in depressed patients. Use of mirtazapine (MIR), an atypical antidepressant approved for the treatment of moderate to severe depression with comorbid anxiety disorders, is associated with significant sedation/somnolence, especially in short-term therapy. Nonetheless, studies with human subjects suggest that MIR-induced sedation is transient, especially when high and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 43 publications
0
12
0
1
Order By: Relevance
“…For this study, the optimal mirtazapine dose (30 mg/kg) was determined in accordance with previous reports. They showed that ⩾30 mg/kg mirtazapine does not affect SLA (Salazar-Juárez et al, 2016) or produce sedation, nor does it induce weight gain (Bittolo et al, 2016; Salazar-Juárez et al, 2017), in rats.…”
Section: Methodsmentioning
confidence: 99%
“…For this study, the optimal mirtazapine dose (30 mg/kg) was determined in accordance with previous reports. They showed that ⩾30 mg/kg mirtazapine does not affect SLA (Salazar-Juárez et al, 2016) or produce sedation, nor does it induce weight gain (Bittolo et al, 2016; Salazar-Juárez et al, 2017), in rats.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, we have previously reported that chronic dosing of 30 mg/kg of mirtazapine does not alter spontaneous locomotor activity (Salazar-Juárez et al, 2016) and/or cause sedation in rats and does not induce weight gain (Salazar-Juárez et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Graves and Napier (2011) found that mirtazapine decreases methamphetamine-seeking in rats. Other authors have shown that mirtazapine attenuates the expression of locomotor sensitization and place preference induced by methamphetamine, morphine, nicotine and cocaine (Barbosa-Méndez et al, 2017b,c;Graves et al, 2012b;Herrold et al, 2009;Salazar-Juárez et al, 2017;Voigt and Napier, 2012;Voigt et al, 2011).…”
Section: Treatment Of Mirtazapine During Extinction On the Re-acquisi...mentioning
confidence: 99%
“…Group I received plain MRT after being suspended in water, group II was given MRT loaded into SBA-15 (optimized formula). Administration was orally by pharyngostomy tube (4 French) and dose equal to 15 mg/kg (El-Sisi et al., 2017 ; Salazar-Juárez et al., 2017 ). Orbital blood samples (0.5 ml) were collected at 0, 0.5, 1, 2, 3, 5, 8, 11, and 24 hours in a heparinized tube, centrifuged at 4000 rpm for 10 min to separate plasma.…”
Section: Methodsmentioning
confidence: 99%